Unraveling the effect of disproportionation of lithium polysulfides on the electrochemical reaction and S utilization in lithium-sulfur battery. (20th April 2022) - Lee, Seungmin; Sim, Kiyeon; Kwon, JunHwa; Seok, Dain; Eom, KwangSup
Abstract: Lithium–sulfur batteries are considered to be high-energy-density batteries for next-generation energy storage systems instead of commercialized lithium-ion batteries. Even though the dissolution of lithium polysulfides in lithium–sulfur batteries and their consequent electrochemical performance degradation have been studied, the chemical reaction between dissolved lithium polysulfides and solid sulfur, which is called disproportionation, has been less emphasized. In this work, disproportionation during electrochemical discharge is identified in lithium-carbon cells with catholyte under practical conditions (the ratio of electrolyte to sulfur is sufficiently low ≈ 4 μL mgsulfur −1 ), and concentration changes by disproportionation are predicted. To quantify the disproportionation in real time, an electrochemical method, which is a constant current/constant voltage test, is proposed from which the chemical/electrochemical kinetic parameters are derived. This enables us to evaluate the equilibrium shifts of disproportionation at different compositions of lithium polysulfides and the consequent changes in charge amount. The suggested methods are further investigated at different applied currents to elucidate the correlation between the disproportionation and S utilization at different applied currents.